Advances in radiation biology. - Augenstein, Leroy G. (Leroy George), 1928-1969; Mason, Ronald; Quastler, Henry (Academic Press, 1964)
Advances in Radiation Biology, Volume 1, provides an overview of the state of knowledge in radiation biology. The book contains six chapters and opens with a review some of the recent work bearing on the nature of the radicals produced in water and on the rates of some of the reactions of the radicals. It also comments on some of the applications of the radical model which have been made. These are followed by a chapter on the process of photosynthesis, covering light absorption and emission by pigments, electromagnetic energy transfer among and between pigment molecules, and the (physical) tr.